The underlying mechanism of kynurenic acid-induced cytoprotection against ischemia/reperfusion injury of cardiac cells - Nógrádi-Halmi Dóra (2026)
Cardiovascular diseases, including myocardial infarction (MI), are leading causes of death globally. Kynurenic acid (KYNA) has been previously shown to improve the survival of cardiac cells exposed to ischemia/reperfusion (I/R), however, the mechanisms laying behind its protective features in the setting of myocardial I/R have not been clarified yet. Hence, our aim was to uncover molecular events enabling the KYNA-derived cardioprotection. In the present thesis, we have demonstrated that KYNA shows antiapoptotic and mitoprotective effects in the setting of cardiac I/R. Based on our findings, the KYNA-induced protection seems to involve the suppression of both intrinsic and extrinsic apoptotic pathways, as well as the maintenance of physiological intramitochondrial Ca2+ levels, preservation of the structural and functional integrity of mitochondria, and reduction of mitochondrial oxidative stress. Furthermore, we have provided evidence suggesting that survival and mitochondrial respiration of cardiac cells treated with Zaprinast (i.e., another G-protein coupled receptor 35 (GPR35) agonist) improved significantly, while inhibition of GPR35 receptor activity in parallel with KYNA treatment diminished the KYNA-induced cytoprotection, suggesting that stimulation of GPR35 receptor mediated pathways contribute substantially to the protective effects of KYNA. As mitochondrial impairment is a cornerstone of cardiac injury and a driver of I/R-induced proapoptotic mechanisms, determining the severity and extent of the cardiac injury, our results demonstrating the mitoprotective and antiapoptotic features of KYNA in the setting of cardiac I/R injury might contribute to the development of novel treatment strategies for MI patients.